The effect of internet use on depressive symptoms in older adults: based on the chain mediating role of physical exercise and self-rated health - Lin, Lu; He, Pingping (Frontiers in Public Health, 2024)
BackgroundDepressive symptoms in older adults have been a major public health problem. Although many studies have suggested a potential relationship between Internet use and depressive symptoms, the underlying mechanisms of this relationship among older adults remain unclear. This study aimed to explore the multiple mediating effects of physical exercise and self-rated health on the relationship between Internet use and depressive symptoms in older adults.MethodsUtilizing the 2020 data from the China Family Panel Studies (CFPS), we assessed the depressive status among the older population through the application of the Ambulatory Self-Rating Depression Scale. To validate the associations, we conducted a Pearson correlation analysis. Furthermore, we constructed a mediating effect model, which aimed to delve into the intricate pathways mediating the influence of Internet usage on depressive symptoms in the older adults. Additionally, we employed a latent class analysis to uncover the intricate heterogeneity of depression among older individuals who do not utilize the Internet, offering insights into the diverse manifestations of this condition.ResultsAfter controlling for age, sex, marital status, chronic disease, and education level, regression results showed that the use of the Internet had a significant direct effect on depressive symptoms in the older adults (β = −0.684, t = −4.318, p < 0.001). Physical exercise and self-rated health significantly affected depressive symptoms in the older adults (β = −0.176, t = −7.939, p < 0.001; β = −0.937, t = −18.681, p < 0.001). Mediating results showed that the mediating effect of physical exercise between Internet use and depressive symptoms in the older adults was −0.220 (95%CI: −0.2877–−0.1598), and the mediating effect of self-rated health between Internet use and depressive symptoms in the older adults was −0.084 (95%CI: −0.1716–−0.0008), and the chain mediation effect was −0.022 (95%CI: −0.0371–−0.0076). The potential profile analysis of depressive symptoms in the older adults without using the Internet showed that they could be divided into three groups, namely, high loneliness—high depression group (7.4%), medium loneliness—moderate depression group (14.7%), and low loneliness—low depression group (77.9%).ConclusionInternet use can directly affect the depressive symptoms of the older adults, and can also indirectly affect the depressive symptoms of the older adults through physical exercise and self-rated health. The depressive symptoms of the older adults who do not use the Internet are heterogeneous and can be divided into three categories. With the popularization of the Internet, the use of the Internet should be promoted for the older adults, and the frequency of physical exercise should be enhanced to achieve physical and mental health.